Porous alumina as well as preparation method and application thereof

Porous alumina is prepared by hydrothermal reaction and acid-adjusting treatment, which solves the problems of wide distribution of porous alumina particle size and irregular morphology in the prior art, and achieves its high thermal stability and uniform coating in lithium-ion battery separators cover.

CN119430242APending Publication Date: 2025-02-14SUZHOU GINET NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411525865.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing preparation process of porous alumina has problems such as wide particle size distribution and irregular morphology, which leads to insufficient thermal stability and high viscosity in its application in lithium-ion battery separators.

Method used

Porous alumina precursors are prepared by hydrothermal reaction, and acid-adjusted in an alkaline environment to control the pH value of the slurry between 7.0 and 8.5, reduce the generation of large particles single crystals, and then solid-liquid separation and drying and calcination to form porous alumina with regular morphology and narrow particle size distribution.

Benefits of technology

The porous alumina has a regular morphology and narrow particle size distribution, which improves its thermal stability and coating uniformity in the lithium-ion battery separator, and avoids the problem of high viscosity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430242A_ABST
    Figure CN119430242A_ABST
Patent Text Reader

Abstract

The invention discloses porous alumina as well as a preparation method and application thereof, and relates to the technical field of porous materials. The preparation method comprises the following steps: firstly, carrying out hydrothermal reaction on aluminum hydroxide slurry containing aluminum hydroxide, aluminum oxide seed crystal and a dispersing agent, enabling porous aluminum oxide precursor slurry obtained by the hydrothermal reaction to be in an alkaline environment, adjusting the pH value of the slurry to 7.0-8.5 through acid adjustment, and then carrying out solid-liquid separation, calcination and other processes. Aluminum ions in the solution can be washed away in the solid-liquid separation (such as filter pressing) process through the acid adjusting process, large-particle single crystals in the porous aluminum oxide precursor are reduced, the obtained porous aluminum oxide precursor is uniform in crystal size, and the monodisperse porous aluminum oxide precursor is prepared through the synthesis section. And after subsequent calcination, the morphology is regular, the particle size distribution is narrower, and the monodisperse porous alumina powder can be obtained only through agglomeration formed by ultrafine scattering and calcination of the jet mill.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of porous materials, and in particular to porous aluminum oxide and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the advantages of large specific capacity and long cycle life, and have been widely used. However, lithium-ion batteries have safety issues, which have not yet been completely resolved. The diaphragm in lithium-ion batteries is a structure located between the positive and negative electrodes, which has a great impact on the safety performance of the battery. Currently, the common diaphragm materials are mainly polyolefins, such as polyethylene, polypropylene, etc. However, the heat resistance temperature of general polyolefin diaphragms is relatively low. After the battery generates heat, the diaphragm will shrink, which will cause battery safety problems.

[0003] In order to improve the thermal stability of the diaphragm, a thermal coating is often applied to the surface of the diaphragm to reduce the thermal shrinkage performance of the diaphragm. The raw materials used for the thermal coating are generally alumina, etc. The introduction of porous alumina into the diaphragm is beneficial to improve the thermal shock resistance of lithium-ion batteries. However, the common porous alumina particle size distribution is wide, ranging from a few microns to tens of microns, and the particle size needs to be controlled by mechanical grinding. Mechanical grinding will destroy the porous structure of porous alumina and form more debris, which will increase the BET.

[0004] Therefore, there is an urgent need to improve the preparation process of porous alumina in order to prepare porous alumina products with regular morphology and narrow particle size distribution.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a porous alumina and a preparation method thereof, aiming at preparing a porous alumina product with regular morphology and narrow particle size distribution.

[0007] Another object of the present invention is to provide the use of porous alumina in the preparation of battery separators or battery pole pieces.

[0008] The present invention is achieved in that:

[0009] In the first aspect, the present invention provides a porous alumina product, wherein the particle size range D50 of the porous alumina product is 0.3 μm-1.0 μm, the particle size D90 is 0.6 μm-2.0 μm, the particle size D99 is 0.9 μm-3 μm, and the specific surface area is 10 m 2 / g-30m 2 / g, pore size is 5nm-50nm.

[0010] In an alternative embodiment, the porous alumina is formed by sintering an intermediate body that does not contain alumina trihydrate;

[0011] and / or, the porous alumina does not contain hexagonal platelets;

[0012] And / or, the porous alumina is a single crystal particle.

[0013] In a second aspect, the present invention provides a method for preparing porous alumina, comprising:

[0014] Aluminum hydroxide slurry containing aluminum hydroxide, aluminum oxide seed crystals and a dispersant is subjected to a hydrothermal reaction to obtain a porous aluminum oxide precursor slurry;

[0015] The porous alumina precursor slurry is acidified to make the pH value of the slurry be 7.0-8.5;

[0016] The acid-adjusted slurry is subjected to solid-liquid separation, and the obtained solid material is used to prepare porous alumina through a calcination process.

[0017] In an optional embodiment, the pH value of the slurry after acid adjustment is controlled to be 7.5-8.0;

[0018] Preferably, the acid used in the acid adjustment process is selected from at least one of an inorganic acid and an organic acid; organic acids include oxalic acid, citric acid, acetic acid and formic acid; inorganic acids include nitric acid, sulfuric acid, phosphoric acid and hydrochloric acid;

[0019] More preferably, the acid solution used in the acid adjustment process is selected from at least one of oxalic acid, citric acid, acetic acid and formic acid; and the concentration of the acid solution is 0.1 mol / L-10.0 mol / L.

[0020] In an optional embodiment, the solid material obtained by solid-liquid separation is sequentially dried, once dispersed and calcined;

[0021] Preferably, the method further comprises: secondarily dispersing the calcined material to obtain monodispersed porous alumina;

[0022] More preferably, the secondary disintegration is performed by air jet milling.

[0023] In an optional embodiment, the calcination temperature is controlled to be 600° C.-1200° C., and the holding time is 0.5 h-5.0 h;

[0024] Preferably, the heating rate during the calcination process is controlled to be 1°C / min-10°C / min;

[0025] Preferably, the powder obtained after the primary breaking is loaded into a sagger for calcination, and the loading amount is controlled to be greater than 90%.

[0026] In an optional embodiment, the water content of the powder is ≤0.3wt% by drying;

[0027] Preferably, the drying is carried out by microwave infrared drying, and the temperature of the microwave temperature zone is controlled to be 90°C-110°C, and the temperature of the infrared temperature zone is controlled to be 120°C-130°C.

[0028] In an optional embodiment, the particles are broken up once by ultrafine breaking, the crushing pressure is controlled to be 0.2 MPa-0.6 MPa, and the frequency of the classifying wheel is 10 Hz-90 Hz;

[0029] Preferably, the solid-liquid separation is carried out by filter pressing and washing, and the water content of the filter cake is controlled to be 60%-80%, and the conductivity of the filter cake is ≤60μs / cm.

[0030] In an optional embodiment, the reaction temperature of the hydrothermal reaction process is controlled to be 180°C-240°C, and the reaction time is 10h-50h;

[0031] Preferably, the reaction pressure of the hydrothermal reaction is 1.5 MPa-3.0 MPa.

[0032] In an optional embodiment, the preparation process of the aluminum hydroxide slurry includes: mixing and grinding aluminum hydroxide, aluminum oxide seed crystals, a dispersant and water;

[0033] Preferably, the mass ratio of aluminum hydroxide to aluminum oxide seed crystals is 100:(0.001-1);

[0034] Preferably, the mass ratio of aluminum hydroxide to dispersant is 100:(0.1-1), and the dispersant is selected from at least one of polyvinyl pyrrolidone, sodium salt of polycarboxylate and hexadecyltrimethylammonium bromide;

[0035] Preferably, the mass ratio of aluminum hydroxide to water is 1:(0.5-4.0).

[0036] In a third aspect, the present invention provides the use of the porous alumina according to the aforementioned embodiment in the preparation of a battery separator or a battery electrode.

[0037] The present invention has the following beneficial effects: the present invention first utilizes aluminum hydroxide slurry containing aluminum hydroxide, aluminum oxide seeds and dispersant for hydrothermal reaction, and the porous aluminum oxide precursor slurry obtained by the hydrothermal reaction is an alkaline environment. The inventor creatively introduces an acid adjustment step to make the pH value of the slurry reach 7.0-8.5, and then performs solid-liquid separation, calcination and other processes. The acid adjustment process can make the aluminum ions in the solution be washed away during the solid-liquid separation (such as by filter pressing) process, reduce the large particle single crystals in the porous aluminum oxide precursor, make the obtained porous aluminum oxide precursor crystal size uniform, and prepare a monodisperse porous aluminum oxide precursor through the synthesis stage. After subsequent calcination, the morphology is regular, the particle size distribution is narrower, and the monodisperse porous aluminum oxide powder can be obtained by only breaking up the agglomerates formed by calcination through air flow milling.

[0038] It should be noted that the hydrothermal reaction stage is a process of dissolution and recrystallization. A certain concentration of aluminum ions will remain in the solution. The porous alumina precursor slurry obtained by the hydrothermal reaction is an alkaline environment. If the slurry is directly filtered and dried without the acid adjustment step, the aluminum ions in the slurry will crystallize and precipitate in the form of aluminum hydroxide in an alkaline environment. The precipitated aluminum hydroxide crystals are large in size, uneven in morphology, and have a wide particle size distribution. The porous alumina precursor powder mixed with aluminum hydroxide has an irregular morphology and a wide particle size distribution after calcination, and the BET increases and the pore size decreases, which will lead to problems such as slurry viscosity and uneven coating in subsequent applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0040] Figure 1 This is a morphology diagram of porous alumina prepared in an embodiment of the present invention;

[0041] Figure 2 This is a morphology diagram of porous alumina prepared in a comparative example of the present invention. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0043] It is generally believed that the poor consistency of the product and the difficulty in drying are due to the problem of too large specific surface area. However, the inventors have found in continuous experiments that when the overall specific surface area is not much different, there is still a problem of poor consistency in particle size and the lower limit of water content after drying is difficult to continue to decrease. The inventors continued to trace the root cause of this problem and finally found that: after the hydrothermal reaction and before drying, alumina trihydrate crystals will precipitate, and the precipitated alumina trihydrate crystals are usually larger and flaky, and the water content is also higher, which will have a certain impact on the specific surface area and particle size of the product. The inventor speculates that the reason for the precipitation of alumina trihydrate crystals is that after cooling and after filter pressing, the solvent content decreases, causing aluminum ions that were not originally precipitated to appear in the form of alumina trihydrate crystals.

[0044] On this basis, the inventors proposed an acid adjustment process to curb the crystallization of aluminum ions after the hydrothermal reaction, and then curb the crystallization of other non-monohydrate alumina, so as to improve the consistency of the product.

[0045] The present invention also provides a method for preparing porous alumina, comprising the following steps:

[0046] S1. Preparation of aluminum hydroxide slurry

[0047] Aluminum hydroxide, aluminum oxide seed crystals, a dispersant and water are mixed and ground to obtain aluminum hydroxide slurry.

[0048] Specifically, the aluminum oxide seed crystals can be commercially available raw materials, and the particle size is nanometer level, such as 10nm-100nm. Aluminum hydroxide contains crystal water, such as aluminum hydroxide trihydrate can be used as raw material.

[0049] In some embodiments, the dispersant is selected from at least one of polyvinyl pyrrolidone, sodium salt of polycarboxylate and cetyltrimethylammonium bromide. The dispersant can be any one or more of the above. The introduction of the dispersant can make the particle distribution more uniform, which is conducive to the preparation of a uniform product.

[0050] Furthermore, the mass ratio of aluminum hydroxide to alumina seed crystals is 100:(0.001-1), the mass ratio of aluminum hydroxide to dispersant is 100:(0.1-1), and the mass ratio of aluminum hydroxide to water is 1:(0.5-4.0). By further adjusting the amount of aluminum hydroxide, alumina seed crystals, dispersant and water, the recrystallization process is better controlled to obtain a uniform porous alumina precursor slurry.

[0051] Specifically, the mass ratio of aluminum hydroxide to aluminum oxide seed crystals can be 100:0.001, 100:0.005, 100:0.010, 100:0.050, 100:0.100, 100:0.500, 100:1.000, etc. The mass ratio of aluminum hydroxide to dispersant can be 100:0.1, 100:0.3, 100:0.5, 100:0.8, 100:1.0, etc. The mass ratio of aluminum hydroxide to water can be 1:0.5, 1:1.0, 1:2.0, 1:3.0, 1:4.0, etc.

[0052] S2. Hydrothermal reaction

[0053] Aluminum hydroxide slurry containing aluminum hydroxide, aluminum oxide seed crystals and a dispersant is subjected to a hydrothermal reaction to obtain a porous aluminum oxide precursor slurry. During the hydrothermal reaction, aluminum hydroxide monohydrate loses water and is recrystallized to obtain a porous aluminum oxide precursor slurry.

[0054] Furthermore, the reaction temperature of the hydrothermal reaction process is controlled to be 180°C-240°C, the reaction time is 10h-50h, and the reaction pressure of the hydrothermal reaction is 1.5MPa-3.5MPa. By further regulating the temperature, time and pressure of the hydrothermal reaction, the reaction is fully carried out to generate aluminum hydroxide particles with uniform particle size.

[0055] Specifically, the hydrothermal reaction can be carried out in a hydrothermal reactor, the temperature of the hydrothermal reaction can be 180°C, 200°C, 240°C, 240°C, etc., the reaction time can be 10h, 20h, 30h, 40h, 50h, etc., and the pressure of the hydrothermal reaction can be 1.5MPa, 2.0MPa, 2.5MPa, 3.0MPa, 3.5MPa, etc.

[0056] S3, acid adjustment

[0057] The porous alumina precursor slurry is acidified to make the pH value of the slurry be 7.0-8.5. Acidification can reduce the large-particle single crystals in the porous alumina precursor and make the crystal size of the porous alumina powder after calcination uniform. Monodisperse porous alumina powder can be obtained by only breaking up the agglomerates formed by calcination through ultrafine airflow grinding.

[0058] Specifically, the pH value of the slurry after acid adjustment can be 7.0, 7.5, 8.0, 8.5, etc.

[0059] In a preferred embodiment, the pH value of the slurry after acid adjustment is controlled to be 7.5-8.0. The pH value of the slurry within this range can further reduce the formation of large-grained single crystals and improve the uniformity of the product particles after calcination.

[0060] In some embodiments, the acid solution used in the acid adjustment process is selected from at least one of an inorganic acid and an organic acid, and the acid solution used can be an inorganic acid, an organic acid, or a mixed acid. Among them, the organic acid includes commonly used organic acids such as oxalic acid, citric acid, acetic acid, and formic acid; the inorganic acid includes commonly used inorganic acids such as nitric acid, sulfuric acid, phosphoric acid, and hydrochloric acid.

[0061] In a preferred embodiment, the acid solution used in the acid adjustment process is selected from at least one of oxalic acid, citric acid, acetic acid, and formic acid, and the acid solution can be any one or more of the above; the concentration of the acid solution is 0.1mol / L-10mol / L (such as 0.1mol / L, 1.0mol / L, 3.0mol / L, 5.0mol / L, 8.0mol / L, 10.0mol / L, etc.). By further regulating the type and concentration of the acid solution, a good regulation effect is achieved without affecting the subsequent calcination step, and the formation of large-particle single crystals can be reduced. Specifically, the use of inorganic acids will introduce a large amount of impurity elements, thereby affecting the purity of the product; the use of organic acids with too long chains will affect the subsequent ablation, and it is appropriate to use short-chain oxalic acid, citric acid, acetic acid, and formic acid.

[0062] S4, solid-liquid separation, drying, and dispersion

[0063] The solid material obtained by solid-liquid separation of the acid-adjusted slurry is then dried and dispersed once. After the once-dispersed powder, a monodispersed porous alumina precursor powder can be obtained, and after calcination, a uniform porous alumina agglomerate is obtained.

[0064] The method of solid-liquid separation is not limited, and may be a filter press washing method, but is not limited thereto. In some embodiments, filter press washing is used for solid-liquid separation, and the water content of the filter cake is controlled to be 60%-80%, such as 60%, 70%, 80%, etc.; the number of washing times and time are adjusted to make the conductivity of the filter cake ≤60μs / cm, so as to fully remove the residual ions on the surface.

[0065] After solid-liquid separation, surface moisture can be fully removed by drying, so that the water content of the powder is ≤0.3wt%, and the water is fully removed after calcination. The drying method is not limited, and a microwave infrared drying method can be used to control the temperature of the microwave temperature zone to 90°C-110°C, and the temperature of the infrared temperature zone to 120°C-130°C. By adjusting the temperature of each zone, the drying process does not affect the crystal morphology of the precursor, and only removes surface moisture. Specifically, the temperature of the microwave temperature zone can be 90°C, 95°C, 100°C, 105°C, 110°C, etc., and the temperature of the infrared temperature zone can be 120°C, 125°C, 130°C, etc.

[0066] Specifically, microwave infrared drying can be operated using an existing microwave infrared dryer, which has a microwave temperature zone and an infrared temperature zone. During the drying process, a large amount of moisture is first removed in the microwave zone for 1-4 hours, and then trace moisture is removed in the infrared zone for 0.5-2 hours.

[0067] In some embodiments, ultrafine breaking can be used for one-time breaking, and the crushing pressure is controlled to be 0.2MPa-0.6MPa, such as 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa, 0.6MPa, etc.; the frequency of the grading wheel is 10Hz-90Hz, such as 10Hz, 20Hz, 30Hz, 40Hz, 50Hz, 60Hz, 70Hz, 80Hz, 90Hz, etc.

[0068] Specifically, ultrafine dispersion is to use a jet crusher to break up the agglomerated powder, and then control the particle size distribution of the powder through a classifier. With the regulation of steps S1-S3, monodisperse porous alumina precursor powder can be obtained after ultrafine classification. The so-called "monodisperse" means that the morphology is regular and the particle size distribution is narrow.

[0069] S5. Calcination

[0070] The solid material obtained in step S4 is calcined to prepare porous alumina agglomerates, which are then dispersed for a second time to obtain a monodisperse porous alumina finished product.

[0071] In some embodiments, the calcination temperature is controlled to be 600°C-1200°C, and the holding time is 0.5h-5.0h. Calcination at this temperature can make aluminum hydroxide fully react to obtain porous aluminum oxide agglomerates. Specifically, the calcination temperature can be 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, etc., and the holding time can be 0.5h, 1.0h, 2.0h, 3.0h, 4.0h, 5.0h, etc. The heating rate of the calcination process can be controlled to be 1°C / min-10°C / min, such as 1°C / min, 3°C / min, 5°C / min, 8°C / min, 10°C / min, etc.

[0072] In actual operation, the powder obtained after the first breaking can be loaded into a sagger for calcination, and the loading amount is controlled to be greater than 90%. The sagger can be a corundum sagger, and the calcination process can be carried out in a calcination furnace.

[0073] In some embodiments, air jet milling can be used for secondary dispersion, and air jet milling can be used for secondary dispersion to prevent damage to the porous structure of porous alumina. Common porous alumina has a wide particle size distribution, and sand milling is usually required to control the particle size, but sand milling destroys the single crystal structure of porous alumina, forming more debris, which increases BET.

[0074] It should be added that the preparation method provided in the embodiment of the present invention prepares a monodisperse porous alumina precursor in the synthesis stage, and subsequently only uses airflow to break up the calcination agglomerates to obtain a monodisperse porous alumina powder. The operation is convenient and has very good industrial application prospects.

[0075] The present invention also provides a porous alumina, which is prepared by the preparation method provided by the present invention. The preparation method is simple and easy to implement, and the obtained porous alumina has a regular morphology and a narrower particle size distribution. The particle size range of the porous alumina product is D50 of 0.3μm-1.0μm, the particle size D90 of 0.6μm-2.0μm, the particle size D99 of 0.9μm-3μm, and the specific surface area of ​​10m 2 / g-30m 2 / g, pore size is 5nm-50nm.

[0076] In some embodiments, the porous alumina is formed by sintering an intermediate that does not contain alumina trihydrate. Since the intermediate does not contain alumina trihydrate crystals with larger particle size and higher water content, the consistency of the product after sintering is better and the particle size distribution is uniform. Specifically, the intermediate is the hydrated oxide before sintering, that is, the product obtained in step S4.

[0077] In some embodiments, the porous alumina does not contain a hexagonal flaky structure. From the electron microscope image, it can be seen that the porous alumina does not contain a hexagonal flaky structure and is a single crystal particle.

[0078] The porous alumina provided in the embodiment of the present invention is used in the preparation of battery separators or battery pole pieces, which is beneficial to further improve the electrochemical performance of the battery.

[0079] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0080] It should be noted that the main raw materials used in the following examples and comparative examples are as follows: aluminum hydroxide is aluminum hydroxide trihydrate, a commercially available raw material; and alumina seed crystals are alumina particles with a particle size of 10-100 nm, a commercially available raw material.

[0081] Example 1

[0082] This embodiment provides a method for preparing porous alumina, comprising the following steps:

[0083] (1) 100 g of aluminum hydroxide, 0.5 g of a dispersant (sodium polycarboxylate), 0.1 g of alumina seed crystals, and 150 g of pure water were placed in a vertical stirred mill and ground for 1 hour to obtain an aluminum hydroxide slurry.

[0084] (2) The aluminum hydroxide slurry obtained in step (1) is put into a hydrothermal reactor, and the reaction temperature is controlled to be 200° C., the reaction time is 20 h, and the pressure is 2.0 MPa to obtain a porous alumina precursor slurry.

[0085] (3) The porous alumina precursor slurry obtained in step (2) was acidified using an aqueous solution of oxalic acid at a concentration of 2 mol / L to adjust its pH to 8.0.

[0086] (4) The slurry obtained in step (3) is subjected to filter pressing and washing to obtain a porous alumina precursor filter cake, the filter cake has a water content of 70%, and the filter cake conductivity is ≤60μs / cm. The porous alumina precursor filter cake is subjected to microwave infrared drying, the microwave temperature zone is controlled at 100°C, and the infrared temperature zone is controlled at 125°C. First, a large amount of water is removed in the microwave zone for 2 hours, and then trace water is removed in the infrared zone for 1 hour. A porous alumina precursor powder is obtained, with a water content of ≤0.3%. The porous alumina precursor powder is ultra-finely broken up, with a crushing pressure of 0.4Mpa and a grading wheel frequency of 50Hz, to obtain a monodispersed porous alumina precursor powder.

[0087] (5) Calcine the porous alumina precursor powder obtained in step (4), and load the powder into a corundum sagger with a loading capacity of 95%. Control the heating rate of the calcining furnace to 3°C / min, the insulation temperature to 900°C, and the insulation time to 3h to obtain porous alumina agglomerates. Use a jet mill to ultrafinely break up the porous alumina agglomerates, control the crushing pressure to 0.4MPa, and the frequency of the grading wheel to 30Hz to obtain a finished porous alumina product.

[0088] Example 2

[0089] This embodiment provides a method for preparing porous alumina, comprising the following steps:

[0090] (1) 100 g of aluminum hydroxide, 0.1 g of a dispersant (polyvinyl pyrrolidone), 0.001 g of alumina seed crystals, and 400 g of pure water were placed in a vertical stirred mill and ground for 1 hour to obtain an aluminum hydroxide slurry.

[0091] (2) The aluminum hydroxide slurry obtained in step (1) is put into a hydrothermal reactor, and the reaction temperature is controlled to be 180° C., the reaction time is 50 h, and the pressure is 1.5 MPa to obtain a porous alumina precursor slurry.

[0092] (3) The porous alumina precursor slurry obtained in step (2) was acidified using an aqueous oxalic acid solution with a concentration of 0.1 mol / L to adjust its pH to 7.0.

[0093] (4) The slurry obtained in step (3) is subjected to filter pressing and washing to obtain a porous alumina precursor filter cake, the filter cake has a water content of 70%, and the filter cake conductivity is ≤60μs / cm. The porous alumina precursor filter cake is subjected to microwave infrared drying, the microwave temperature zone is controlled at 90°C, and the infrared temperature zone is controlled at 120°C. A large amount of water is first removed in the microwave zone for 4 hours, and then trace water is removed in the infrared zone for 2 hours. A porous alumina precursor powder is obtained, with a water content of ≤0.3%. The porous alumina precursor powder is ultra-finely broken up, with a crushing pressure of 0.2Mpa and a grading wheel frequency of 10Hz, to obtain a monodispersed porous alumina precursor powder.

[0094] (5) Calcine the porous alumina precursor powder obtained in step (4), and load the powder into a corundum sagger with a loading capacity of 95%. Control the heating rate of the calcining furnace to 1°C / min, the insulation temperature to 600°C, and the insulation time to 5h to obtain porous alumina agglomerates. Use a jet mill to ultrafinely break up the porous alumina agglomerates, control the crushing pressure to 0.2Mpa, and the frequency of the grading wheel to 10Hz to obtain a porous alumina finished product.

[0095] Example 3

[0096] This embodiment provides a method for preparing porous alumina, comprising the following steps:

[0097] (1) 100 g of aluminum hydroxide, 1 g of a dispersant (polyvinyl pyrrolidone), 1 g of alumina seed crystals, and 50 g of pure water were placed in a vertical stirred mill and ground for 1 hour to obtain an aluminum hydroxide slurry.

[0098] (2) The aluminum hydroxide slurry obtained in step (1) is put into a hydrothermal reactor, and the reaction temperature is controlled to be 240° C., the reaction time is 10 h, and the pressure is 3.5 MPa to obtain a porous alumina precursor slurry.

[0099] (3) The porous alumina precursor slurry obtained in step (2) was acidified using 10 mol / L oxalic acid solution to adjust its pH to 8.5.

[0100] (4) The slurry obtained in step (3) is subjected to filter pressing and washing to obtain a porous alumina precursor filter cake, the filter cake has a water content of 70%, and the filter cake conductivity is ≤60μs / cm. The porous alumina precursor filter cake is subjected to microwave infrared drying, the microwave temperature zone is controlled at 110°C, and the infrared temperature zone is controlled at 130°C. First, a large amount of water is removed in the microwave zone for 1 hour, and then trace water is removed in the infrared zone for 0.5 hour. A porous alumina precursor powder is obtained, and the water content is ≤0.3%. The porous alumina precursor powder is ultra-finely broken up, the crushing pressure is 0.6Mpa, and the classification wheel frequency is 90Hz, to obtain a monodispersed porous alumina precursor powder.

[0101] (5) Calcine the porous alumina precursor powder obtained in step (4), and load the powder into a corundum sagger with a loading capacity of 95%. Control the heating rate of the calcining furnace to 10°C / min, the insulation temperature to 1200°C, and the insulation time to 0.5h to obtain porous alumina agglomerates. Use a jet mill to ultrafinely break up the porous alumina agglomerates, control the crushing pressure to 0.6Mpa, and the frequency of the grading wheel to 90Hz to obtain a porous alumina finished product.

[0102] Example 4

[0103] The only difference from Example 1 is that after the acid is adjusted in step (3), the pH is 7.0.

[0104] Example 5

[0105] The only difference from Example 1 is that after acid adjustment in step (3), pH=8.5.

[0106] Example 6

[0107] The only difference from Example 1 is that the acid solution used in step (3) is a 10 mol / L acetic acid aqueous solution.

[0108] Example 7

[0109] The only difference from Example 1 is that the acid solution used in step (3) is a 2 mol / L citric acid aqueous solution.

[0110] Comparative Example 1

[0111] The only difference from Example 1 is that step (3) is not performed, that is, step (4) is performed directly after step (2).

[0112] Comparative Example 2

[0113] This comparative example uses aluminum hydroxide for direct calcination, and the specific steps refer to step (5) of Example 1.

[0114] Test Example 1

[0115] The SEM morphology of the aluminum oxide products prepared in Test Example 1 and Comparative Example 1 is as follows: Figure 1 and Figure 2 shown.

[0116] from Figure 1 It can be seen that the particle size of the alumina product prepared in the embodiment of the present invention is very uniform, and the porous alumina does not contain hexagonal flake structures; Figure 2 It can be seen that the particle size of the aluminum oxide product prepared in Comparative Example 1 is obviously uneven, and contains hexagonal flake structures. Figure 1 and Figure 2 It can be seen from the comparison that the particle size distribution of the porous alumina precursor can be regulated by adjusting the acid in the present invention, and monodisperse porous alumina powder can be obtained by air flow crushing.

[0117] Test Example 2

[0118] The particle size distribution, specific surface area and pore size of the alumina products prepared in the test examples and comparative examples are shown in Table 1.

[0119] Table 1 Particle size distribution, specific surface area and pore size of alumina products

[0120]

[0121]

[0122] It can be seen that the particle size distribution of the aluminum oxide product prepared in the embodiment of the present invention is obviously narrower and the pore size is larger.

[0123] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A porous alumina, characterized in that: The particle size range of porous alumina products is D50 0.3μm-1.0μm, particle size D90 0.6μm-2.0μm, particle size D99 0.9μm-3μm, and specific surface area is 10m 2 / g-30m 2 / g, pore size is 5nm-50nm.

2. The porous alumina according to claim 1, characterized in that The porous alumina is formed by sintering an intermediate body that does not contain alumina trihydrate; and / or, the porous alumina does not contain hexagonal sheet structures; And / or, the porous alumina is single crystal particles.

3. A method for preparing the porous alumina according to claim 1 or 2, characterized in that: include: Aluminum hydroxide slurry containing aluminum hydroxide, aluminum oxide seed crystals and a dispersant is subjected to a hydrothermal reaction to obtain a porous aluminum oxide precursor slurry; The porous alumina precursor slurry is acidified to make the pH value of the slurry be 7.0-8.5; The acid-adjusted slurry is subjected to solid-liquid separation, and the obtained solid material is used to prepare porous alumina through a calcination process.

4. The preparation method according to claim 3, characterized in that: The pH value of the slurry after acid adjustment is controlled to be 7.5-8.0; Preferably, the acid used in the acid adjustment process is selected from at least one of an inorganic acid and an organic acid; the organic acid includes oxalic acid, citric acid, acetic acid and formic acid; the inorganic acid includes nitric acid, sulfuric acid, phosphoric acid and hydrochloric acid; More preferably, the acid solution used in the acid adjustment process is selected from at least one of oxalic acid, acetic acid and phosphoric acid; and the concentration of the acid solution is 0.1 mol / L-10 mol / L.

5. The preparation method according to claim 3 or 4, characterized in that: The solid material obtained by solid-liquid separation is sequentially dried, once dispersed and calcined; Preferably, the method further comprises: secondarily dispersing the calcined material to obtain monodispersed porous alumina; More preferably, the secondary breaking up is performed by air jet milling.

6. The preparation method according to claim 5, characterized in that: Control the calcination temperature to 600℃-1200℃ and the holding time to 0.5h-5.0h; Preferably, the heating rate during the calcination process is controlled to be 1°C / min-10°C / min; Preferably, the powder obtained after the primary breaking is loaded into a sagger for calcination, and the loading amount is controlled to be greater than 90%.

7. The preparation method according to claim 5, characterized in that: The moisture content of the powder is ≤0.3wt% by drying; Preferably, the drying is carried out by microwave infrared drying, and the temperature of the microwave temperature zone is controlled to be 90°C-110°C, and the temperature of the infrared temperature zone is controlled to be 120°C-130°C.

8. The preparation method according to claim 5, characterized in that: The primary breaking is carried out by ultra-fine breaking, the crushing pressure is controlled to be 0.2MPa-0.6MPa, and the frequency of the classifying wheel is 10Hz-90Hz; Preferably, the solid-liquid separation is carried out by filter pressing and washing, and the water content of the filter cake is controlled to be 60%-80%, and the conductivity of the filter cake is ≤60μs / cm.

9. The preparation method according to claim 3, characterized in that: The reaction temperature of the hydrothermal reaction process is controlled to be 180°C-240°C, and the reaction time is 10h-50h; Preferably, the reaction pressure of the hydrothermal reaction is 1.5MPa-3.0MPa; Preferably, the preparation process of the aluminum hydroxide slurry comprises: mixing and grinding aluminum hydroxide, the aluminum oxide seed crystals, the dispersant and water; Preferably, the mass ratio of aluminum hydroxide to the aluminum oxide seed crystal is 100:(0.001-1); Preferably, the mass ratio of aluminum hydroxide to the dispersant is 100:(0.1-1), and the dispersant is selected from at least one of polyvinyl pyrrolidone, sodium salt of polycarboxylate and hexadecyltrimethylammonium bromide; Preferably, the mass ratio of aluminum hydroxide to water is 1:(0.5-4.0).

10. Use of the porous alumina according to any one of claims 1 to 2 or the porous alumina prepared by the preparation method according to any one of claims 3 to 9 in preparing battery separators or battery pole pieces.

Citation Information

Cited By

  • Monodisperse alpha-al2o3 microspheres and method for preparing the same

    CN122789426A